2022
DOI: 10.1002/asia.202200181
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium(III) Porphyrinoid Phototheranostics

Abstract: Molecular phototheranostics as an emerging field of modern precision medicine has recently attracted increasing research attention owing to non‐invasiveness, high precision, and controllable nature of light. In this work, we reported promising gadolinium (Gd3+) porphyrinoids as phototheranostic agents for magnetic resonance imaging (MRI) and photodynamic therapy (PDT). The synthesized Gd‐1‐4‐Glu featured with meso‐glycosylation and β‐lactonization to endow good biocompatibility and improved photophysical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Under this circumstance, polar groups will play a vital role in transmitting the relaxation. 50 For GBCAs with q > 0, the contribution of inner-sphere relaxation to r 1 should be considered. Theoretically, the greater the q value, the higher the inner-sphere relaxivity; however, more coordinated water molecules will greatly destroy the stability of chelates, increasing the risk of releasing toxic Gd( iii ) ions.…”
Section: Resultsmentioning
confidence: 99%
“…Under this circumstance, polar groups will play a vital role in transmitting the relaxation. 50 For GBCAs with q > 0, the contribution of inner-sphere relaxation to r 1 should be considered. Theoretically, the greater the q value, the higher the inner-sphere relaxivity; however, more coordinated water molecules will greatly destroy the stability of chelates, increasing the risk of releasing toxic Gd( iii ) ions.…”
Section: Resultsmentioning
confidence: 99%
“…191 In 2022, the Zhang group reported glycosylated cis -( 74 )/ trans ( 75 )-Gd porphodilactones as ‘proof-of-concept’ dual modal MRI and PDT theranostic systems. 192 Owing to regioisomerism, the ostensibly related isomers showed different r 1 relaxivities (4.3 ± 0.2 mM −1 s −1 for 74 and 2.8 ± 0.2 mM −1 s −1 for 75 ) under 0.5 T, 37 °C. Of note, 75 exhibited substantial red-shifted absorption beyond 660 nm and robust generation of reactive oxygen species, including 1 O 2 and radicals (O 2 ˙ − and ˙OH), that engaged in both Type II and Type I PDT pathways.…”
Section: Other Theranosticsmentioning
confidence: 94%
“…Recently, Jin et al reported the synthesis of a series of water-soluble Gd(III)-porphyrinoids ( 60a-c ), which showed suitability as new phototheranostics based on PDT and MRI. The designed compounds contained meso -glycosylation and β -lactonization features, to improve their photophysical properties, solubility and biocompatibility 119 . Hereby, compound 60c showed the best NIR light-harvesting properties, as well as a similar ROS generation and higher photostability than the clinical photosensitizer methylene blue, and was thus chosen for an in-depth investigation.…”
Section: Mri and Pdtmentioning
confidence: 99%